A new strategy to realize high comprehensive energy storage properties in lead-free bulk ceramics. Issue 26 (10th June 2019) - Qu, Ning; Du, Hongliang; Hao, Xihong
Abstract : A new strategy (coexistence of nanodomains and PNRs via composition optimization) was proposed to achieve high comprehensive energy storage properties in lead-free bulk ceramics. Abstract : Lead-free bulk ceramics have attracted increasing interest for electrical energy storage in pulsed power systems because of their superior mechanical properties, environment-friendliness, high power density and fast charge/discharge rate. Although considerable efforts have been made to design a large amount of lead-free bulk ceramics for energy storage applications, there is still a lack of scientific and feasible guidelines of how to explore new material systems with large recoverable energy density ( W rec ), high energy storage efficiency ( η ) and excellent thermal stabilty, which are the three key parameters for energy storage applications. In this work, a strategy (coexistence of nanodomains and polar nanoregions via composition optimization) was proposed to achieve high comprehensive energy storage properties in lead-free bulk ceramics. NaNbO3 –Bi(Mg0.5 Zr0.5 )O3 ceramics were selected as an example to verify the feasibility of this strategy. Encouragingly, both a high W rec of 2.31 J cm −3 and a high η of 80.2% were achieved in 0.93NaNbO3 –0.07Bi(Mg0.5 Zr0.5 )O3 (0.93NN–0.07BMZ) ceramics under 255 kV cm −1, while keeping excellent thermal stability over 20 °C to 170 °C with the variation of W rec < 10%, which is superior to other reported lead-free bulk ceramics. Compared with other lead-free bulk ceramics, the 0.93NN–0.07BMZ ceramic is a promising material for high-temperature pulsed power capacitors. Most importantly, this work provides a significant guideline for exploring a series of new high-performance lead-free dielectric ceramics for next generation advanced pulsed power capacitors in the future.